2011
DOI: 10.1007/s10578-011-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and Depressive Symptoms in Preadolescence

Abstract: This study examined associations among several measures of emotion regulation, and their links to depressive symptoms, in a sample of children ages 10-12 years old (N=87). Both temporal features of emotion regulation and regulation processes involved in the evaluation, monitoring, and modification of emotion were assessed through parent and child report and behavioral observation. Children also completed a self-report measure of depressive symptoms. Children with more depressive symptoms were reported by mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…From infancy through early adulthood, the preference for this or that coping strategy is likely to change as a function of individual experiences with, and knowledge about, the likely outcome of this or that strategy -e.g., recurring to social support or employing a problem-solving approach. Since we might hypothesize that adolescence is a very crucial period in the development and maturation of coping strategies, the analysis of such strategies may help us better understand individual differences in psychosocial well-being and adjustment [3], the onset of psychosocial difficulties and psychopathology development [15,16,17,18,19], and, in the end, may help us prevent problems linked with the use of dysfunctional coping (and/or regulation) strategies in adulthood.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…From infancy through early adulthood, the preference for this or that coping strategy is likely to change as a function of individual experiences with, and knowledge about, the likely outcome of this or that strategy -e.g., recurring to social support or employing a problem-solving approach. Since we might hypothesize that adolescence is a very crucial period in the development and maturation of coping strategies, the analysis of such strategies may help us better understand individual differences in psychosocial well-being and adjustment [3], the onset of psychosocial difficulties and psychopathology development [15,16,17,18,19], and, in the end, may help us prevent problems linked with the use of dysfunctional coping (and/or regulation) strategies in adulthood.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…A review of recent discussion in relevant literature indicated that depressive individuals used inappropriate or ineffective emotion regulation strategies; they had difficulties using cognitive control; they had difficulties processing negative material/situation (where greater regression was experienced, reappraisal was reduced, and suppression was increased); and they had negative judgments of self-expression (Compare, Zarbo, Shonin, Gordon, & Marconi, 2014). For instance, Siener and Kerns (2012) examined the relationships between emotion regulation and depressive symptoms in children aged 10-12 and found that children with depressive symptoms had difficulties regulating emotions. Also, depressive patients were found to use internal dysfunctional emotion regulation strategies such as rumination and suppression very often and, however, internal functional emotion regulation strategies such as reappraisal very rarely (Arditte & Joormann, 2011; Campbell-Sills, Barlow, Brown & Hofmann, 2006;Gross & John, 2003;Smith & Alloy, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of regulation processes and strategies in adolescence, a critical period for their development, seems instead crucial to better understand individual differences in adolescents' well-being and adjustment (Silk et al, 2003;Silvers et al 2012), and which factors are likely to account for the onset of psychosocial difficulties and psychopathology development (Aldao et al, 2010;Nolen-Hoekesema & Aldao, 2011;Siener & Kerns, 2012;Silk et al, 2003), possibly providing indications for the prevention of problems linked with dysfunctional regulation later on in adulthood.…”
Section: Introductionmentioning
confidence: 99%